2001
DOI: 10.1002/lsm.1104
|View full text |Cite
|
Sign up to set email alerts
|

Shape retention in porcine‐septal cartilage following Nd:YAG (λ = 1.32 μm) laser‐mediated reshaping

Abstract: While laser heating does significantly reshape cartilage, clinical use of this technology will require "overbending" of the cartilage graft to compensate for this memory effect. The degree of overbending is likely to vary with cartilage type and location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
(17 reference statements)
1
22
0
Order By: Relevance
“…In our study, after 10 days, this curvature remains stable with an average shape retention at 6 weeks of 64 AE 4% and this value is very similar to those obtained by Gray et al who observed a shape retention varying from 58 to 75% [7]. Moreover, our technique did not necessitate any ablation of the skin before performing the laser irradiation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our study, after 10 days, this curvature remains stable with an average shape retention at 6 weeks of 64 AE 4% and this value is very similar to those obtained by Gray et al who observed a shape retention varying from 58 to 75% [7]. Moreover, our technique did not necessitate any ablation of the skin before performing the laser irradiation.…”
Section: Discussionsupporting
confidence: 77%
“…In 1993, Sobol et al demonstrated cartilage reshaping using a laser was possible and pioneered the use of lasers for the correction of cartilaginous deformities in the head and neck [1][2][3]. Several wavelengths have since been evaluated: Diode laser (l ¼ 0.98 mm) [4], Nd:YAG laser (l ¼ 1.32 mm and l ¼ 1.44 mm) [5][6][7], Ho:YAG laser (l ¼ 2.1 mm) [8], Er:YAG laser (l ¼ 2.94 mm) [9] and CO 2 laser (l ¼ 10.6 mm) [10]. Recently, Ovchinnikov et al have performed a clinical series of 110 patients who underwent in situ laser nasal septal cartilage reshaping [11].…”
Section: Introductionmentioning
confidence: 99%
“…The delivery of additional reagents to fuel the electrochemical reactions depends upon diffusion from the bulk of the cartilage sample, and this process dominates the reaction and dictates the magnitude of the electric current. 12,30 Multiplication both sides of the Cottrell Equation (2) by a √ t yields a parameter, S:…”
Section: Discussionmentioning
confidence: 99%
“…The reshaping angle was measured after rehydration again. 12 Surface of the specimens was examined using a dissection microscope to observe electrode position of electrode material onto the cartilage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation